Transport Variability of Very Short Lived Substances From the West Indian Ocean to the Stratosphere. Issue 10 (29th May 2018) - Fiehn, Alina; Quack, Birgit; Marandino, Christa A.; Krüger, Kirstin
Abstract: Halogen‐ and sulfur‐containing compounds are supersaturated in the surface ocean, which results in their emission to the atmosphere. These compounds can be transported to the stratosphere, where they impact ozone, the background aerosol layer, and climate. In this study we calculate the seasonal and interannual variability of transport from the West Indian Ocean (WIO) surface to the stratosphere for 2000–2016 with the Lagrangian transport model FLEXPART using ERA‐Interim meteorological fields. We investigate the transport relevant for very short lived substances (VSLS) with tropospheric lifetimes corresponding to dimethylsulfide (1 day), methyl iodide (CH3 I, 3.5 days), bromoform (CHBr3, 17 days), and dibromomethane (CH2 Br2, 150 days). The stratospheric source gas injection of VSLS tracers from the WIO shows a distinct annual cycle associated with the Asian monsoon. Over the 16‐year time series, a slight increase in source gas injection from the WIO to the stratosphere is found for all VSLS tracers and during all seasons. The interannual variability shows a relationship with sea surface temperatures in the WIO as well as the El Niño–Southern Oscillation. During boreal spring of El Niño, enhanced stratospheric injection of VSLS from the tropical WIO is caused by positive sea surface temperature anomalies and enhanced vertical uplift above the WIO. During boreal fall of La Niña, strong injection is related to enhanced atmospheric upward motion over the East Indian Ocean and a prolonged Indian summer monsoon season. Related physical mechanisms and uncertainties are discussed in this study. Key Points: The Lagrangian model FLEXPART/ERA‐Interim transports very short lived substances (VSLS) from the West Indian Ocean to the stratosphere Source gas injection of VSLS above 17 km reveals a distinct annual cycle associated with the Asian monsoon Interannual variability of stratospheric VSLS source gas injection is influenced by West Indian Ocean sea surface temperatures, as well as by ENSO